2016
DOI: 10.4236/cs.2016.76073
|View full text |Cite
|
Sign up to set email alerts
|

Surface Area Estimation, Volume Change Detection in Lime Stone Quarry, Tirunelveli District Using Cartosat-1 Generated Digital Elevation Model (DEM)

Abstract: The objective of the study was to estimate the change detection in a surface area and volume analysis of the lime stone quarry for the year 2006 and 2014 in Mannur, Tirunelveli district, Tamilnadu. Though the mining activities are essential for the cement factory, it depletes the ground water table and causes pollution to the Environment. The Integration of Remote Sensing and GIS are effective for analyzing the impact of quarrying on natural resources. In this study, Cartosat-1 satellite data generated Digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, studies on quarry monitoring remain temporally limited. Whether using several decades of spanned space-borne imagery or higher resolution images focusing on a short time scale, prior studies have generally relied on a comparison of imagery from two to three time slices [1,5,6,9,10]. Hence, with the focus on scarce observations so far, the socioeconomic reasons behind these quarry changes have not been thoroughly analyzed.…”
Section: Social Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies on quarry monitoring remain temporally limited. Whether using several decades of spanned space-borne imagery or higher resolution images focusing on a short time scale, prior studies have generally relied on a comparison of imagery from two to three time slices [1,5,6,9,10]. Hence, with the focus on scarce observations so far, the socioeconomic reasons behind these quarry changes have not been thoroughly analyzed.…”
Section: Social Discussionmentioning
confidence: 99%
“…Today, remote sensing with its capability of establishing calibrated observations over decadal-scale time periods and at sufficiently high spatial resolution (≤30 m) can provide this information to achieve better insight into quarry dynamics. Several local and regional studies have focused on the dynamics of quarries using a variety of remotely-sensed datasets with various spatial and temporal resolutions [1,[3][4][5][6][7][8][9][10]. The findings from these studies have demonstrated the ability of remote sensing to detect and analyze the magnitude and spatial changes of natural environments as a result of mining activities [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excavated areas, stockpiles, and quarry waste negatively impact landscape form, affecting the visual appeal of BMNP. Excavation leaves depressions forming potential hazardous ponds, particularly in the summer season [75] (Figure 10). Focus group discussions highlight residents' observations regarding landscape change, land degradation, and deforestation of Afro-Alpine vegetation.…”
Section: Major Causes and Drivers Of Red Ash Excavation And Its Envir...mentioning
confidence: 99%
“…This data may now be obtained by remote sensing, It has the potential to create calibrated observations with an appropriate geographic resolution with decadal time scale. The dynamics of quarries have been the subject of several local and regional studies utilising a range of remotely sensed datasets with different spatial and temporal resolutions (Bonifazi et al 2003;Karuppasamy et al 2016;Koruyan et al 2012;Latifovic et al 2005;C. C. Liu et al 2005;Nikolakopoulos et al 2010;Nikolakopoulos and Raptis 2014;Saroglu et al 2005;Uça et al 2011).…”
Section: Introductionmentioning
confidence: 99%